Fungsi Kreativitas Guru Pendidikan Agama Islam dalam Meningkatkan Prestasi dan Hasil Belajar Siswa - Jannah, Eni Miftahul; Sinaga, Devi Yusnila; Khoir, Muhammad Ikhsanul; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
Learning is an activity carried out by someone intentionally and in a conscious state to be able to gain an understanding or new knowledge so that a person experiences relatively good behavior changes in thinking and acting in everyday life. The rise of teachers who only carry out their profession as teachers but forget the obligations and nature of a teacher. In addition, many teachers ignore creativity as Islamic religious education teachers, this is necessary so that student achievement and learning outcomes can improve the quality of their learning. The research in this article uses a qualitative research method developed (Library Research). The results of this study are that creativity in learning that is applied by Islamic religious education teachers can have many positive impacts during learning that affect increased results and achievement in learning. For example in increasing the interest of students in developing the skills or expertise they have. The creativity of Islamic religious education teachers can build everything that has a positive impact on students which makes them enthusiastic and active in learning.